2014
DOI: 10.1590/0074-0276140066
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastroenteritis and enteric viruses in hospitalised children in southern Brazil: aetiology, seasonality and clinical outcomes

Abstract: Viral acute gastroenteritis (AG) is a significant cause of hospitalisation in children younger than five years. Group A rotavirus (RVA) is responsible for 30% of these cases. Following the introduction of RVA immunisation in Brazil in 2006, a decreased circulation of this virus has been observed. However, AG remains an important cause of hospitalisation of paediatric patients and only limited data are available regarding the role of other enteric viruses in these cases. We conducted a prospective study of paed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 57 publications
1
39
1
9
Order By: Relevance
“…Similar evidence of mixed infections was evident in other HAdV epidemiological studies conducted in other parts of the globe. [42][43][44] Many epidemiology studies demonstrated that many HAdVs types can be found in stool due to prolonged shedding in the feces after a previous infection, 28,38,45 the Department for International Development, UK (UK Aid). We gratefully acknowledge these donors for their support and commitment to icddr,b's research efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar evidence of mixed infections was evident in other HAdV epidemiological studies conducted in other parts of the globe. [42][43][44] Many epidemiology studies demonstrated that many HAdVs types can be found in stool due to prolonged shedding in the feces after a previous infection, 28,38,45 the Department for International Development, UK (UK Aid). We gratefully acknowledge these donors for their support and commitment to icddr,b's research efforts.…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8] Among seven subgenera, subgenus HAdV-F representing type 40 and 41 is associated with acute gastroenteritis; the incidence ratio is higher in low-or middle-income countries (2-31%) compared to the highincome countries (1-8%). [9][10][11][12] Other subgenera such as HAdV-A (types 12, 18, and 31), 13 HAdV-C (types 1, 2, and 5), and HAdV-D (types 28,29,30,32,37,[43][44][45][46]), [14][15][16] and HAdV-G (type 52) 17 have also been identified sporadically in patients with gastroenteritis, however, their role in causing diarrhea remains unclear.…”
mentioning
confidence: 99%
“…Although this study was conducted during a 1‐year period, the results are consistent with Brazilian data confirming the incidence of RVA mainly in the winter and spring (June to August and September to November) and NoV in the summer (December to February). However, there is considerable controversy regarding the seasonality of NoV in Brazil, mainly because it is a country of continental dimensions and, consequently, of diverse climates …”
Section: Discussionmentioning
confidence: 99%
“…Reference strains are identified by genotype|GenBank accession number followed by genogroup or subgroup February) 32. However, there is considerable controversy regarding the seasonality of NoV in Brazil, mainly because it is a country of continental dimensions and, consequently, of diverse climates 33. Factors such as low income, poor access to education, poor hygiene, and low nutritional and immune status might be responsible for the high prevalence of AGE in the child population.…”
mentioning
confidence: 99%
“…This study confirms these reports as Adv40 was not detected. Detection of these Adv serotypes in sewage final effluents is health threatening [53,54].…”
Section: Discussionmentioning
confidence: 99%